2018
DOI: 10.1021/acs.est.8b01001
|View full text |Cite
|
Sign up to set email alerts
|

How Persistent and Bioavailable Are Oxygenated Deepwater Horizon Oil Transformation Products?

Abstract: About half of the surface oil floating on the Gulf of Mexico in the aftermath of the 2010 Deepwater Horizon spill was transformed into oxygenated hydrocarbons (OxHC) within days to weeks. These OxHC persist for years in oil/sand aggregates in nearshore and beach environments, and there is concern that these aggregates might represent a long-term source of toxic compounds. However, because this OxHC fraction is a continuum of transformation products that are not well chemically characterized, it is not included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…Once again this could be due to carbon and energy storage, or the persistence of trace amounts of high molecular weight PAHs. Alternatively, hydrocarbons can be undetected through analytical methods such as GC-MS ( McKenna et al, 2013 ) when weathered hydrocarbons from an oil spill undergo transformation into oxygenated hydrocarbons (though currently there is no evidence that Cycloclasticus is able to degrade oxygenated hydrocarbons) ( Kiruri et al, 2013 ), which can persist for years within oil/sand aggregates ( Aeppli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again this could be due to carbon and energy storage, or the persistence of trace amounts of high molecular weight PAHs. Alternatively, hydrocarbons can be undetected through analytical methods such as GC-MS ( McKenna et al, 2013 ) when weathered hydrocarbons from an oil spill undergo transformation into oxygenated hydrocarbons (though currently there is no evidence that Cycloclasticus is able to degrade oxygenated hydrocarbons) ( Kiruri et al, 2013 ), which can persist for years within oil/sand aggregates ( Aeppli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…While OHCB have been demonstrated to degrade other compounds in pure culture (Radwan et al, 2019;Zadjelovic et al, 2020), there is still limited evidence that the OHCB are competitive for non-hydrocarbon substrates in the environment. This is evidenced by the fact OHCB are typically present in extremely low numbers in uncontaminated environments but rapidly increase in abundance following oil-spills (Yakimov et al, 2004a;Atlas and Hazen, 2011;Acosta-González et al, 2015;Nogales and Bosch, 2019). Therefore, while it is evident that OHCB use a few other carbon and energy sources, for clarity we refer to them hereafter as "OHCB" to distinguish between these highly adapted and competitive hydrocarbon degraders and those more metabolically diverse bacteria, which can also degrade hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Second, partially oxidized OC can be traced at a molecular-level using mass spectrometry (e.g., Aeppli et al, 2018;Cao & Tarr, 2017;Cory et al, 2010;Ruddy et al, 2014). The strength of mass spectrometry is two-fold: it is sensitive and provides insights into the diverse array of compounds produced by sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…The major weaknesses of this approach are difficulties in quantifying molecular abundance and the costs of specialized equipment and personnel. Coupled gas‐ or liquid‐chromatography with quadrupole or time‐of‐flight mass spectrometry techniques have been applied to quantify partial photo‐oxidation products; however, only a small fraction of total products was quantifiable (<1%) even with multiple derivatization steps, and the analysis remains costly and highly specialized (Aeppli et al, ; Cao & Tarr, ).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical process of photo-oxidation has emerged to be an equally important process to evaporation; a recent lab study has shown that exposure of oil to solar radiation can cause photo-chemical weathering of oil, causing significant changes in the chemical composition of light crude oil within a few days [10]. In addition, based on photo-oxidation of oil under ultraviolet irradiation conducted in the lab, Appeli et al [11] reported that the partial photo-oxidation of oil on the water surface led to 50% of the weathered saturates and aromatics being transformed to oxygenated hydrocarbons within 10 days during the Deepwater Horizon oil spill. The eventual fate (months to years) of the remaining oil is influenced by biological processes involving microorganisms (e.g.…”
Section: Introductionmentioning
confidence: 99%